Some integral characteristics of the earth atmosphere - G, Batsukh; D, Gangbaatar; D, Khaltar; N, Tugjisuren (Scientific transaction of the National University of Mongolia. Physics, 2022)
Atmosphere transparency is one of an important geophysical characteristics of the Earth atmosphere. It characterizes physical state of the Earth atmosphere and immediately has been connected with processes taken place in the atmosphere, moreover not only general synoptic, also formations under the influence of local conditions.